ATTENDANCE APPLICATIONS AS EMPLOYEE ASSESSMENT USING VISUAL FOX PRO 6 - Naomi Azis; Cut Asiana Gemawaty, Skom, MMSI (Jurnal Sistem Informasi, 2003)
In the scope of the accuracy of start or end of working hours is essential in acompany. For companies that use the attendance system. A good attendance system isable to record the presence or absence of the employees in detail.With the above reasons the application is made to provide accurate and detailedreports on PT. Swadharma Griyasatya. And of the complete report is expected to helpcompanies, especially the personnel to provide assessments for their employees.